Environmental sensing and morphological plasticity in plants. (November 2018) - Mizutani, Miya; Kanaoka, Masahiro M.
Abstract: All creatures on earth are affected by their surrounding environment. Animals can move and escape unfavorable environmental changes, whereas plants must respond to environmental stimuli. Plants adapt to changes with cellular-level responses to short-term environmental changes, but may adapt to changes in the environment by regulating their development and growth. In this review, we considered changes in atmospheric CO2 concentrations, dry/wet moisture conditions, flooding, and temperature as examples of environmental stimuli. We mainly focused on leaf morphology and stomatal density as examples of developmental and growth patterns of plants in response to the environment.